If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(2x + 5) + -1 = 2(x + 1) Reorder the terms: -1(5 + 2x) + -1 = 2(x + 1) (5 * -1 + 2x * -1) + -1 = 2(x + 1) (-5 + -2x) + -1 = 2(x + 1) Reorder the terms: -5 + -1 + -2x = 2(x + 1) Combine like terms: -5 + -1 = -6 -6 + -2x = 2(x + 1) Reorder the terms: -6 + -2x = 2(1 + x) -6 + -2x = (1 * 2 + x * 2) -6 + -2x = (2 + 2x) Solving -6 + -2x = 2 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -6 + -2x + -2x = 2 + 2x + -2x Combine like terms: -2x + -2x = -4x -6 + -4x = 2 + 2x + -2x Combine like terms: 2x + -2x = 0 -6 + -4x = 2 + 0 -6 + -4x = 2 Add '6' to each side of the equation. -6 + 6 + -4x = 2 + 6 Combine like terms: -6 + 6 = 0 0 + -4x = 2 + 6 -4x = 2 + 6 Combine like terms: 2 + 6 = 8 -4x = 8 Divide each side by '-4'. x = -2 Simplifying x = -2
| 30=10x+40 | | -30i=22.5 | | a^2=695 | | 2(2m+5)=m+13 | | xy+2x+3x^2=8 | | 4k+1=17 | | 14+21n=28 | | 10x=20whatisx | | 22x-8-18x+3=18x-4-14x+14 | | 5.8x+1=4.8x | | 6x+6-8x=14-16x+14x-8 | | 3x-4=9x | | (Y+4)+2=4Y | | -8(-5u+2y-1)= | | X^14-25= | | -11+x=x+17 | | x^2-2xa+1=0 | | x^2-2ax+1=0 | | 7w-28= | | 7y-9=-15+y | | 6x-17=-7 | | 7x(2x+8)-4(2x-9)= | | (Y+3)+3=4Y | | 7(2.5)+n=17.5 | | -2.2c=-1.2 | | 3+49x=28x+9 | | 0=4+6t-16t^2 | | H(t)=4+6t-16t^2 | | (4x+9)(x-5)=16x+36 | | 32-R=73 | | (x-8)(y-8)=64 | | H(t)=4+6t-16t |